An introduction to the theory of statistics - Alexander Mcfarlane Mood; Kendall, Maurice G. (London : C. Griffin & company, limited, 1946)
An introduction to modern seismological theory, with emphasis on both the physical models and the mathematical descriptions of earthquakes and their sources. It includes a theory of earthquake sources, and seismic wave travel through complex geological zones and viscous and anisotropic media.
Includes index
aia 19/09/17
Loans
Keywords: Mathematical Statistics; Statistics